Perspektif sobural terhadap tindakan pornografi yang dilakukan anak di media sosial - Olivia Womtiseli Naomi Marantika; Sherly Adam; Yonna Beatrix Salamor (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2022)
Introduction: This article discusses the soburural perspective on the acts of pornography committed by children on social media.Whether we realize it or not that most social media has spectacles or pages that are not worth watching by children such as pornography and this will dilute social and religious values. The presence of the internet is often seen as a medium that has an influence on the values adopted by society so that it results in disorganization. This kind of social condition turned out to be also supported by the formation of a layer of power in the mastery of internet technology so that gradually a condition of society that did not obey the rules was formed. Sobural theory that actually brings an understanding of the problem of criminal acts of pornography through the internet is not directed at the formation of a new culture through the attitude of abandoning old cultural values and accepting new cultural values, or adaptation to new cultural valuesPurposes of the Research:  This article aims to analyze the sobural perspective on pornographic acts committed by children on social media and the impacts arising from pornographic acts committed by children on social media. discusses criminal law enforcement against the development of IT (internet) and gadgets that allow the transfer and transmission of pornographic material quickly and directly accessible to childrenMethods of the Research: Research methods used with normative juridical research type. The problem approach used is the legislation approach, the concept analysis approach, the case approach. Sources of legal materials used are primary legal materials and secondary legal materials. The collection technique is through literature studies and is further analyzed through the way of description using qualitative methods.Results of the Research: The results showed that the sobural perspective on pornographic acts committed by children on social media was not in accordance with social, cultural and structural values. As well as the impact of pornographic acts committed by children on social media are addiction, damage to the brain, decreased intellectual level, the desire to try and imitate, start doing pornographic actsgrfi.